The optimal kinematic model of the performance of the clear hip circle to handstand on the uneven bars - a case study - Petkovic, E.; Velickovic, S.; Kolar, E.; Stankovic, R.; Stankovic, D. (Facta Universitatis: Series Physical Education and Sport, 2018)
The aim of this research was to define the optimal kinematic parameters of performance of the Clear hip circle to handstand on uneven bars (KOVT). The optimal kinematic model defined in this case study represents an example of the successful performance of the Clear hip circle to handstand on the uneven bars. The exercise was performed at the 39th and 40th World Cup in Artistic gymnastics in Maribor (SLO). The kinematic parameters were specified by the APAS 3-D video system (Ariel Dynamics Inc., San Diego, CA), using 16 anthropometric reference points and 8 body segments (Foot, Ankle, Knee joint, Hip joint, Wrist, Elbow joint, Shoulder joint and Head), in which one of the points represents the center of gravity of the body. The female gymnasts (N=15), mean age 17.5 yrs, who performed one Clear hip circle on the uneven bars performed two KOVTs in their gymnastics routine, while the rest performed one KOVT on the uneven bars, mean age 17.5. The main method in this research was kinematic, and the additional one was statistical. Optimizing the technique of successful performance of the KOVT is important for detecting different styles of the technique that occur in female gymnasts.